2003
DOI: 10.1038/sj.bmt.1704384
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning with busulfan and fludarabine with or without antithymocyte globulin in HLA-identical sibling transplantation – a retrospective analysis

Abstract: Summary:It is unknown whether the addition of antithymocyte globulin (ATG) to reduced-intensity conditioning with busulfan (BU) and fludarabine (FLU) is beneficial in HLA-identical sibling transplantation. Therefore, we analyzed retrospectively data on 83 patients, who received peripheral blood stem cells from HLA-identical siblings after conditioning with either 8 mg/kg BU and 150 mg/m 2 FLU (n ¼ 45) or 8 mg/kg BU, 180 mg/m 2 FLU and 40 mg/ kg ATG (n ¼ 38). Graft-versus-host disease (GVHD) prophylaxis consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…In this prospective study, we showed that a combination of fludarabine (180 mg/m 2 ) and oral busulfan (8 mg/kg), despite the omission of antithymocyte globulin from the original regimen by Slavin et al [6], can be successfully used to help prepare patients older than 50 years with hematological malignancies for HSCT from an HLA-matched related donor: All patients achieved sustained engraftment without graft failure, only an insignificant occurrence of RRT and treatment-related complications were seen, and PS and dietary intake were well maintained, which agrees with published observational studies on RIST with fludarabine and busulfan [16,22,23].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this prospective study, we showed that a combination of fludarabine (180 mg/m 2 ) and oral busulfan (8 mg/kg), despite the omission of antithymocyte globulin from the original regimen by Slavin et al [6], can be successfully used to help prepare patients older than 50 years with hematological malignancies for HSCT from an HLA-matched related donor: All patients achieved sustained engraftment without graft failure, only an insignificant occurrence of RRT and treatment-related complications were seen, and PS and dietary intake were well maintained, which agrees with published observational studies on RIST with fludarabine and busulfan [16,22,23].…”
Section: Discussionsupporting
confidence: 79%
“…G-CSF mobilized peripheral blood stem cells may have been associated with an increased incidence of GvHD, particularly in its chronic form [34,35]. Conditioning regimen excluded antithymocyte globulin was also a possible explanation of this finding [23]. Most importantly, patients undergoing RIST are usually older than those undergoing CIST, which leads to a higher risk for GvHD [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9] The nucleoside analogue fludarabine has already been incorporated into a variety of reduced-intensity or nonmyeloablative conditioning regimens. [10][11][12] The substance is characterized by high activity against lymphoid neoplasms and has a favorable toxicity profile. 13 Its immunosuppressive effects, particularly on T-cell activity, makes the substance suitable as part of a RIC regimen before allogeneic SCT.…”
Section: Introductionmentioning
confidence: 99%
“…3 With regard to family donors, instead, ATG-F has been used with bone marrow, 6 while in peripheral blood SCT, it has been almost exclusively associated with reducedintensity conditioning (RIC). 8 No data, however, are available for myeloablative, HLAidentical sibling PBSC transplants. We prospectively planned a prospective phase II study on the use of ATG- Table 1 Patients' characteristics and outcome F for the prophylaxis of GVHD after PBSC sibling transplants in CML.…”
mentioning
confidence: 99%